Peningkatan Minat Siswa terhadap Teknologi Kelautan melalui Demonstrasi Robot Bawah Air - Noorman Rinanto; Imam Sutrisno; Petrisia Widyasari Sudarmadji; Antonius Edy Kristiyono (CV. Creative Tugu Pena, 2024)
This research examines the effectiveness of using underwater robot demonstrations as a learning medium to increase students' interest in marine technology. The research was conducted using a quasi-experimental method on MAN 2 Madiun students. The experimental group took part in the underwater robot demonstration, while the control group did not. The results showed that students in the experimental group experienced a significant increase in interest in marine technology compared to the control group. These findings suggest that live demonstrations are an effective method for increasing students' interest in complex topics such as marine technology. underwater robot demonstrations have a significant influence in increasing students' interest in marine technology. Students who took part in the demonstration experienced a much greater increase in interest compared to the control group who did not receive similar treatment.